2009
DOI: 10.1016/j.cageo.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Four interacting aspects of a geological survey knowledge system

Abstract: The developing cyberinfrastructure affects the knowledge system by which geological surveys collect, represent, and communicate their knowledge, and thereby influences their view of the geology. Consequences for four interacting aspects of the overall system (infrastructure, business models, geological framework, and surveying methods) are outlined. Although each reflects a different area of expertise, all aspects must work together to support an incipient change of emphasis in survey work -from publishing map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…It supposes also to fix technological issues raised by the complexity of this approach implying the shift from relational databases to ontological formal languages that offer the possibility of encoding the complexity of knowledge production to create geological maps (Montovani et al, 2020). Results of several studies propose different ways to use this technology to manage similar information (Brodaric, 2004;Balestro and Piana, 2007;Loudon, 2009Loudon, , 2011Giboin et al, 2013) that should be considered in future works.…”
Section: Discussionmentioning
confidence: 99%
“…It supposes also to fix technological issues raised by the complexity of this approach implying the shift from relational databases to ontological formal languages that offer the possibility of encoding the complexity of knowledge production to create geological maps (Montovani et al, 2020). Results of several studies propose different ways to use this technology to manage similar information (Brodaric, 2004;Balestro and Piana, 2007;Loudon, 2009Loudon, , 2011Giboin et al, 2013) that should be considered in future works.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that both statistical and logical methods contribute to the convergent work of data science, and the next-generation scientists should be aware of the KG developments in addition to the overwhelming ML and DL studies. As a reflection, earlier publications in geoinformatics and geomathematics have also addressed the importance of machine-readable knowledge models in the cyberinfrastructure (e.g., Loudon, 2000Loudon, , 2009 and the flexible application of data-driven and knowledge-driven approaches in data analysis (e.g., Bonham-Carter, 1994;Carranza, 2009). However, comparing with the many recent review papers on ML and DL in geosciences, there is a shortage of summary and review of KGs in geosciences.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that geological mapping largely consists in a process of inferencing (Brodaric, 2004;Balestro & Piana, 2007;Loudon, 2009; because, in geology, rocks often document events that are inferred to have occurred, and not directly observed .…”
Section: Introductionmentioning
confidence: 99%
“…"Geologists make sense of their observations by integrating them with through reasoning and interpretation"(Loudon, 2009) …”
mentioning
confidence: 99%